Efektivitas Kompres Air Hangat dan Air Dingin terhadap Penurunan Intensitas Nyeri pada Remaja Putri dengan Dismenore - Amalia, Amrina Rosyadana; Susanti, Yulia; haryanti, Dwi (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2020)
Dysmenorrhea is pain during or before the start of menstruation. The incidence of dysminorrhea in adolescents in Central Java by 2015 is estimated to be 12% to 35% of teenagers, while in Kendal regency as many as 11,565 people (29.8%). Methods of hot and cold water compress ispart of the non-pharmacological methods that are effective, easy, and cheap to overcome dysmenorrheal pain. The purpose of this research was to know the difference of warm water compress and cold water compress to decrease pain intensity of adolescent girl with dysmenorrhea in MAN Kendal. This research usei Quasi Experimental design with Pretest-Posttest design, Non-Equivalent Control Group Design. The sample in this study is 17 people in each treatment group whith was collected with the reasareh uset questeonnare bowbonais as researeh instrument pair schale.the consecutive sampling. Data analysis used Wilcoxonand Man Withn. The results showed that there was a difference in pain intensity before and after being given warm water compresses in adolescent girls with dysmenorrhea in MAN Kendal (p value 0.000 <0.05). There was a difference in pain intensity before and after being given cold water compresses on adolescent girls with dysmenorrhea at MAN Kendal (p value 0.000 <0.05). Warm water compresses are more effective at reducing the intensity of pain than cold water compresses in adolescent girl with dysmenorrhea at MAN Kendal. It is expected that adolescent girls who experience dysmenorrhea can use warm compress cold water compress therapy independently when experiencing dysmenorrhea pain that can reduce the consumption of painkillers.